AgCl/Ag/g-C3N4 Hybrid Composites: Preparation, Visible Light-Driven Photocatalytic Activity and Mechanism - Bao, Yongchao; Chen, Kezheng (Nano-Micro Letters, 2015)
The ternary plasmonic AgCl/Ag/g-C3N4 photocatalysts were successfully fabricated by a modified deposition–precipitation method, through which Ag/AgCl nanoparticles (5–15 nm in size) were evenly dispersed on the surface of g-C3N4. The AgCl/Ag/g-C3N4 composites exhibited higher photocatalytic activity than Ag/AgCl and g-C3N4. The enhanced photocatalytic performance could be attributed to an efficient separation of electron–hole pairs through a Z-scheme mechanism, in which Ag nanoparticles acted as charge separation centers.